Application aquaponics biofloc of sangkuriang catfish (Clarias sp.) - Yonarta, Danang; Malik, Deri; Fitrani, Mirna; Rarassari, Madyasta Anggana (Acta Aquatica: Aquatic Sciences Journal, 2023)
The value of catfish production in Indonesia has decreased drastically every year. Increasing stocking density can be a solution to increase production, but it will have a negative impact on decreasing water quality which will also disrupt catfish production. Therefore, it needs to be accompanied by the application of biofloc and aquaponics technology which plays a role in maintaining optimal water quality while providing additional natural feed (floc) which can reduce feed use and reduce water usage. This study aims to increase the production value of sangkuriang catfish through the application of biofloc and aquaponic systems. This research was conducted in October-November 2022 at the Raudhatul Ulum Sakatiga Agribusiness Group, Ogan Ilir Regency. This study was designed using a comparison experiment. The treatments given consisted of P0 (control), P1 (Maintenance of sangkuriang catfish aquaponic biofloc of kale plant), and P2 (Maintenance of Sangkuriang catfish aquaponic biofloc of lettuce plant). The results showed that P2 was the best treatment which resulted in absolute growth in weight and length of 7.18 g and 3.74 cm, survival of 98%, and growth in length of kale of 30.9 cm.Keywords: aquaponics; biofloc; sangkuriang catfish